Effect of Water Hyacinth Fiber Length and Content on the Torsional Strength of Epoxy Resin Composites - Putratama Aziz Pramana; Muhamad Fitri; Abdul Hamid; Dedik Romahadi (Universitas Mercu Buana, 2024)
This study investigates the influence of water hyacinth fiber length and content on the torsional strength of epoxy resin composites. Utilizing an experimental design, specimens were prepared with varying fiber lengths (10 mm, 20 mm, 25 mm, and 135 mm) and content percentages (4%, 7%, and 10%) and subjected to torsional testing according to ASTM E-143 standards. The primary objective was to determine the optimal fiber configurations that enhance the composite's mechanical properties, particularly its resistance to torsional stress. Results indicated that shorter fiber lengths consistently yielded higher torsional strength, with the 20 mm fibers at a 7% content displaying the highest torque resistance, achieving a maximum of 1.418 Nm and a shear stress of 29.348 MPa. In contrast, longer fibers generally showed diminished performance, likely due to poorer resin penetration and fiber-matrix bonding. Regression analysis was employed to develop predictive models for the torsional behavior based on fiber dimensions and compositions, achieving high accuracy with coefficients of determination (R²) ranging from 0.95 to 1.00, suggesting excellent model fits. These findings underscore the potential of using water hyacinth fibers as effective reinforcement in epoxy composites, particularly at optimal lengths and concentrations. The study contributes to the broader utilization of natural fibers in composites, offering a sustainable alternative to synthetic fibers with beneficial mechanical properties and environmental impacts.